PENGARUH HARGA DAN FAKTOR EKSTERNAL TERHADAP PERMINTAAN EKSPOR KOPI DI INDONESIA - Lukman Lukman (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2012)
The objectives of the research are to know the influence relative price and external factor i.e. exchange rate, and real GDP exporting country of volume Indonesia export coffee. The data used in this research is secondary data in forms of time series. Analytical method used in the study is Ordinary Least Square method. The result of this research indicated that relative price, Real GDP, and lag export volume are affected significantly and positively upon of volume export. Exchange rate affected non-significantly upon of Indonesia export coffee to United States. While for England: Exchange rate and lag export volume affected significantly and positively upon of volume export. Relative price and Real GDP do not affected significantly upon of volume Indonesia export coffee. If the relative price changed and external factors (i.e. foreign price, exchange rate, real GDP exporting country) will influenced to Indonesian total export coffee.DOI: 10.15408/sjie.v1i2.2602